Synthesis and Investigation of Surface Active Properties of Counterion Coupled Gemini Surfactants. Issue 3 (26th July 2013) - Noori, Sahar; Naqvi, Andleeb Zehra; Ansari, Wajid Husain; Akram, Mohd; Kabir‐ud‐Din,
Abstract: Three counterion coupled gemini (cocogem) surfactants in the series 1, 6‐bis( N, N ‐alkyldimethylammonium) adipate, referred as n ‐6‐ n ( n = 12, 14, 16), were synthesized, purified and characterized by 1 H NMR and 13 C NMR. Their physicochemical properties were investigated by electrical conductivity and surface tension measurements. The degree of ionization, critical micelle concentration (CMC), surface excess at the air/solution interface (Γmax ), minimum area per surfactant molecule at the air/solution interface ( A min ), surface tension at the CMC ( γ CMC ), and p C 20 (negative log of the surfactant molar concentration, required to reduce the surface tension of water by 20 mN m −1 ) were calculated. Increase in tail length of the surfactants increases the efficiency of surfactants to decrease the surface tension of water. Thermodynamic parameters, viz. molar free energy at the maximum adsorption attained at CMC ( G min ), standard Gibb's energy of micellization ( Δ G mic o ), and standard Gibbs energy of adsorption ( Δ G ad o ), were also calculated. The Δ G mic o and Δ G ad o values show that the monomers were preferred to be adsorbed at the air/water interface and then in the micellar formation in the bulk. Additionally, fluorescence measurements were used to find the aggregation number. Other relevant surface properties (Krafft point, emulsion stability, foaming ability, micellar stability and dye solubilization ability) were also evaluated. These results suggest that with respect to emulsion formation, micellar stability and dye solubilization, the cocogem with a 16‐carbon chain gives better results, producing 89 % more stable foams and shows better aggregational behavior.